Host Factors and Pathways Involved in the Entry of Mosquito-Borne Alphaviruses. Issue 7 (July 2021) - De Caluwé, Lien; Ariën, Kevin K.; Bartholomeeusen, Koen
Abstract : Chikungunya virus (CHIKV) is an arthropod-borne virus that has re-emerged recently and has spread to previously unaffected regions, resulting in millions of infections worldwide. The genus Alphavirus, in the family Togaviridae, contains several members with a similar potential for epidemic emergence. In order for CHIKV to replicate in targeted cell types it is essential for the virus to enter these cells. In this review, we summarize our current understanding of the versatile and promiscuous steps in CHIKV binding and entry into human and mosquito host cells. We describe the different entry pathways, receptors, and attachment factors so far described for CHIKV and other mosquito-borne alphaviruses and discuss them in the context of tissue tropism and potential therapeutic targeting. Highlights: In the replication cycle of alphaviruses, the entry step is the first essential step to allow efficient production of new viral particles. The main entry pathway of alphaviruses is clathrin-mediated endocytosis. Fusion requires a low pH and takes place in the endosome. However, other, clathrin-independent, pathways that facilitate alphavirus entry have also been described. Some host factors that can mediate alphavirus entry have been identified but entry in the absence of these host factors is still possible. Alphavirus entry appears to be a promiscuous process following multiple routes where various pathways, attachment factors, and receptors can be used, assuring a broad tissue tropism.